A molecular diagnostic tool to replace larval culture in conventional faecal egg count reduction testing in sheep. - Florian Roeber (Public Library of Science (PLoS), 2012)
The accurate diagnosis of parasitic nematode infections in livestock (including sheep and goats) is central to their effective control and the detection of the anthelmintic resistance. Traditionally, the faecal egg count reduction test (FECRT), combined with the technique of larval culture (LC), has been used widely to assess drug-susceptibility/resistance in strongylid nematodes. However, this approach suffers from a lack of specificity, sensitivity and reliability, and is time-consuming and costly to conduct. Here, we critically assessed a specific PCR assay to support FECRT, in a well-controlled experiment on sheep with naturally acquired strongylid infections known to be resistant to benzimidazoles. We showed that the PCR results were in close agreement with those of total worm count (TWC), but not of LC. Importantly, albendazole resistance detected by PCR-coupled FECRT was unequivocally linked to Teladorsagia circumcincta and, to lesser extent, Trichostrongylus colubriformis, a result that was not achievable by LC. The key findings from this study demonstrate that our PCR-coupled FECRT approach has major merit for supporting anthelmintic resistance in nematode populations. The findings also show clearly that our PCR assay can be used as an alternative to LC, and is more time-efficient and less laborious, which has important practical implications for the effective management and control strongylid nematodes of sheep.